The effect of behavioral motivation and accounting information on stock investment decision making - Sigalingging, Eni Duwita (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2023)
The purpose of this study was to analyze how much positive and significant influence the influence of Self-image/ firm image, Social relevance, Advocate recommendation, Personal financial needs and Accounting information in making stock investment decisions. This type of research is causality research. The population is retail investors taken from the existing securities market in Indonesia. The sample of this research data is 50 samples. The data analysis method is SEM-PLS. The results showed that accounting information, self-image/firm, social relevance, advocate recommendations and personal financial needs had a significant positive effect on stock investment decisions. This means that the higher the level of selfconfidence, self/firm image, social relevance, Advocate recommendations and one's personal financial needs, the higher that person is in making stock investment decisions.